Signficantly improving magnetic properties of Sr-La-Co hexagonal ferrite - Nguyen, Khanh Dung (H. : ĐHQGHN, 2017)
The hard magnetic ferrite system has been prepared by traditional ceramic technology and showed hexagonal crystalline structure. The anisotropic sample has the best hard magnetic properties. The role of La and Co as well as the reasons leading to these perfect properties of the studied ferrites have been discussed based on the overall studies of structure and characteristics of examined samples.